2023
DOI: 10.1002/esp.5648
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic dune distribution, morphology and activity during the last 20 000 years: A global overview

Abstract: Parabolic dunes form and migrate in almost every climate and geographic zones of the world, ranging from the tropical coastlines to the arid continental deserts. Despite their extensive distribution and their importance within the aeolian sediment landscape, the understanding of their morphological development, activity and link with climates remains somewhat limited to local or regional scales. A good understanding of the present climate conditions under which parabolic dunes are formed and/or reactivated wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 305 publications
(556 reference statements)
0
1
0
Order By: Relevance
“…Given that TAR and LMR have been used with increasing frequency and are debated in the literature, it is clear that a systematic review of these terms is needed. Typical approaches to reviewing a bedform KOS would involve enumerating the types of bedforms under consideration and all of the hypotheses for their formation (e.g., Filhol & Sturm, 2015; Zhao & Gao, 2021; Vimpere, 2023). However, while reviewing the literature on TARs and LMRs, we found that this conventional review structure was not productive because, as we will argue in this critical review, these terms do not actually represent types of bedform.…”
Section: Introductionmentioning
confidence: 99%
“…Given that TAR and LMR have been used with increasing frequency and are debated in the literature, it is clear that a systematic review of these terms is needed. Typical approaches to reviewing a bedform KOS would involve enumerating the types of bedforms under consideration and all of the hypotheses for their formation (e.g., Filhol & Sturm, 2015; Zhao & Gao, 2021; Vimpere, 2023). However, while reviewing the literature on TARs and LMRs, we found that this conventional review structure was not productive because, as we will argue in this critical review, these terms do not actually represent types of bedform.…”
Section: Introductionmentioning
confidence: 99%
“…Such information can be used not only to enhance our understanding of natural processes but also to develop effective strategies for safeguarding coastal areas [5]. By examining dune dynamics, researchers can gain a greater understanding of how environmental factors have impacted the evolution of arid dune formations over time [7]. Ultimately, the knowledge from such studies can inform critical decisions related to land use, resource management, conservation efforts, and risk control [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that over extended periods of time, variations in wind direction have the potential to result in a noticeable left-or right-handed asymmetry in the morphology of dunes. Conversely, short-term changes such as those occurring daily tend to produce smaller and wider shapes [7]. Consequently, the ground slope of dunes can differ considerably, giving rise to an ideal environment for the growth of vascular plants.…”
Section: Introductionmentioning
confidence: 99%